Pelatihan SPSS pada Guru-Guru di Sekolah Dasar Negeri 173529 Tampahan - Simanjuntak, Sinta Dameria; Usman, Ari (Jurnal Pemberdayaan Masyarakat, 2020)
The teachers at SD 173529 are teachers with the status of Civil Servants (PNS). Teachers with the status of civil servants must write scientific papers when going up to a position or class. The problem is writing scientific papers and data processing. The solution offered to overcome this problem is SPSS training include processing research data and how to read the SPSS output to be narrated in the research results. The method used consisted of group discussions, deliberations, in-house training and workshops. The results from this activity are the teacher gives a positive response to the training activities include 100% of teachers liked the training material, the modules used, the way of learning, the way the instructor taught. The other results are the teachers stated that the training material is new (71.42%), the modules used are new (85.71%), the learning method implemented is new (85.71%), the method of teaching is a new way of teaching (85,71%), the teacher expressed interest in using SPSS in processing research data and in training activities (100%).